Ultramorphology of the metapleural gland in three species of Atta (Hymenoptera, Formicidae) - De Gusmão, Luciana G.; Caetano, Flávio Henrique [UNESP]; Nakano, Octavio (My University, 2001)
Differences among the metapleural glands of four female castes of Atta bisphaerica Forel, 1908, A. capiguara Gonçalves, 1944 and A. sexdens rubropilosa Forel, 1908 were examined by scanning electron microscope. There were no differences in gland size between the same castes of these species, although the opening gland in A. sexdens rubropilosa had been twice as large as A. bisphaerica. The relative size and functional significance of the metapleural gland among different castes is discussed and similarities between these and the other Formicidae till now studied is presented.
Keywords: Atta; Metapleural gland; Morphology